Composite current collector with high interfacial adhesion and method for preparing the same
Patent Information
- Application Number
- CN202610836788.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本发明的目的之一在于提供一种高界面结合力的复合集流体,以解决现有技术中复合集流体的金属层与胶粘层之间界面结合力不足的问题
1.本发明通过在第一金属层表面设计微纳沟槽结构、在第二金属层表面设计微纳凸起结构,与界面增强层和功能胶粘层形成微纳互锁结构,显著增加了界面接触面积,提高了机械互锁作用,使界面结合力提高40%-60%,有效防止了金属层与胶粘层之间的分离现象。第一金属层和第二金属层的厚度精确控制在0.01μm-3μm范围内,使金属层兼具足够的导电性和机械强度,同时显著减轻了重量。金属层厚度减少的同时,大幅提高了电池能量密度,且具有优异的柔韧性和抗断裂性能平衡。
Smart Images

Figure CN123017978A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery manufacturing technology, specifically relating to a composite current collector with high interfacial bonding and its preparation method. Background Technology
[0002] With the rapid development of new energy vehicles and the energy storage industry, higher requirements have been placed on the energy density, safety, and cycle life of lithium-ion batteries. Composite current collectors, as a new type of battery material, have received widespread attention in recent years due to their high safety and high energy density characteristics. Traditional composite current collectors typically adopt a sandwich structure of "metal layer - polymer material base film layer - metal layer", in which the polymer material base film layer (such as PP, PET, etc.) serves as the intermediate support layer, and metal layers (copper or aluminum) are plated on both sides.
[0003] However, existing composite current collectors have significant drawbacks: the interfacial bonding between the polymer base film layer and the metal layer is weak, leading to metal layer detachment during battery use, severely impacting battery cycle performance and safety. Chinese patent application CN117832502A discloses a composite current collector that eliminates the polymer base film layer and uses an adhesive layer to directly connect the two metal layers, improving interfacial bonding. However, this technical solution still has the following problems: 1. The improvement in interfacial bonding between the metal layer and the adhesive layer is limited. In actual tests, the peel strength only increased by about 20%-30%, and interfacial separation may still occur during battery charge and discharge cycles.
[0004] 2. Uneven stress distribution at the interface between the adhesive layer and the metal layer can easily lead to localized stress concentration during battery manufacturing and use, resulting in microcracks and affecting long-term reliability.
[0005] 3. The adhesive layer in the prior art is usually a homogeneous structure, which cannot effectively alleviate the difference in thermal expansion coefficient between the metal layer and the adhesive layer, resulting in large stress at the interface when the temperature changes.
[0006] 4. In the preparation process of composite current collectors in the prior art, the surface of the metal layer is smooth, and the mechanical interlocking effect with the adhesive layer is weak, which limits the further improvement of the interfacial bonding force.
[0007] Currently, how to further improve the interfacial bonding force between the metal layer and the adhesive layer in composite current collectors, while solving problems such as uneven interfacial stress distribution and differences in thermal expansion coefficients, has become a technical challenge that urgently needs to be addressed in this field. Summary of the Invention
[0008] One of the objectives of this invention is to provide a composite current collector with high interfacial bonding strength, so as to solve the problem of insufficient interfacial bonding strength between the metal layer and the adhesive layer of the composite current collector in the prior art.
[0009] The second objective of this invention is to provide a method for preparing a composite current collector with high interfacial bonding strength, which achieves efficient preparation of the composite current collector through specific process steps and parameter control.
[0010] The objective of this invention can be achieved through the following technical solutions: A composite current collector with high interfacial bonding strength comprises, in the thickness direction, a first metal layer, an interface reinforcement layer, a functional adhesive layer, and a second metal layer, wherein micro-nano interlocking structures are formed between the first metal layer and the interface reinforcement layer, and between the functional adhesive layer and the second metal layer; the interface reinforcement layer is composed of metal oxide modified with nanoparticles, with a thickness of 0.005 μm-0.5 μm; the functional adhesive layer is composed of modified polyvinylidene fluoride and nanofillers, with a thickness of 0.1 μm-5 μm; and the thicknesses of the first metal layer and the second metal layer are 0.01 μm-3 μm, respectively.
[0011] Furthermore, the materials of the first metal layer and the second metal layer are independently selected from one or more of aluminum, copper, nickel, titanium, silver, or their alloys.
[0012] Furthermore, in the nanoparticle-modified metal oxide of the interface enhancement layer, the nanoparticles are one or more of silicon dioxide, aluminum oxide, or zirconium oxide, with a particle size of 5nm-50nm, and the amount added is 0.1%-5% of the total mass of the metal oxide.
[0013] Furthermore, in the functional adhesive layer, the modified polyvinylidene fluoride is carboxylated polyvinylidene fluoride or hydroxylated polyvinylidene fluoride, and the nanofiller is one or more of carbon nanotubes, graphene or boron nitride, with an addition amount of 0.01%-2% of the total mass of the adhesive.
[0014] Furthermore, the micro / nano structure on the surface of the first metal layer is a trench structure with a depth of 0.005 μm-0.1 μm and a width of 0.01 μm-0.5 μm, and the trench density is 50-500 trenches / μm. 2 The micro / nano structure on the surface of the second metal layer consists of protrusions with a height of 0.005 μm-0.1 μm and a diameter of 0.01 μm-0.5 μm, with a protrusion density of 50-500 per μm. 2 .
[0015] Furthermore, the metal oxide in the interface enhancement layer is one or more of aluminum oxide, titanium oxide, or silicon oxide.
[0016] Furthermore, the composite current collector is applied to the positive or negative electrode of a lithium-ion battery, wherein when applied to the negative electrode, the first metal layer is copper or a copper alloy, and the second metal layer is copper or a copper alloy; when applied to the positive electrode, the first metal layer is aluminum or an aluminum alloy, and the second metal layer is aluminum or an aluminum alloy.
[0017] A method for preparing a composite current collector with high interfacial bonding strength as described above includes the following steps: S1. A first metal layer is deposited on both sides of the first release film by physical vapor deposition, and the surface of the first metal layer is subjected to laser microstructure treatment to form a micro-nano trench structure. S2. An interface reinforcement layer is formed on the surface of the first metal layer by atomic layer deposition, and the interface reinforcement layer is subjected to plasma treatment. S3. Coat the interface reinforcement layer with a functional adhesive layer to form a first semi-finished product comprising, in sequence, a functional adhesive layer, an interface reinforcement layer, a first metal layer, a first release film, a first metal layer, an interface reinforcement layer, and a functional adhesive layer. S4. Apply the second release film to both sides of the first semi-finished product to form the second semi-finished product; S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, perform corona treatment on the peeling surface of the second release film, and deposit a second metal layer on the surface of the functional adhesive layer by physical vapor deposition, forming a micro-nano protrusion structure on the surface of the second metal layer. S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0018] Furthermore, the parameters for laser microstructure processing described in S1 are: laser wavelength 266nm-1064nm, pulse width 10ps-100ns, and energy density 0.1J / cm². 2 -5J / cm 2 The scanning speed is 50mm / s-500mm / s, and the scanning spacing is 5μm-50μm.
[0019] Furthermore, the process parameters for forming the interface enhancement layer by atomic layer deposition in S2 are as follows: deposition temperature 80℃-200℃, precursor is trimethylaluminum, titanium tetrachloride or tetraethoxysilane, reaction chamber pressure 10Pa-100Pa, pulse time 0.01s-1s, purging time 1s-10s, and number of cycles 5-100; the parameters for plasma treatment are as follows: oxygen flow rate 10sccm-100sccm, power 50W-500W, treatment time 10s-120s, and treatment distance 5mm-20mm.
[0020] The beneficial effects of this invention are: 1. This invention designs micro-nano trench structures on the surface of the first metal layer and micro-nano protrusion structures on the surface of the second metal layer, forming a micro-nano interlocking structure with the interface reinforcement layer and functional adhesive layer. This significantly increases the interfacial contact area, enhances the mechanical interlocking effect, and improves the interfacial bonding force by 40%-60%, effectively preventing separation between the metal layer and the adhesive layer. The thicknesses of the first and second metal layers are precisely controlled within the range of 0.01μm-3μm, ensuring that the metal layers possess both sufficient conductivity and mechanical strength while significantly reducing weight. The reduced metal layer thickness significantly improves the battery energy density and achieves an excellent balance between flexibility and fracture resistance.
[0021] 2. This invention uses nanoparticle-modified metal oxide as the interface reinforcement layer. The addition of nanoparticles not only improves the mechanical strength of the interface reinforcement layer but also enhances its compatibility with the metal layer and functional adhesive layer, forming a gradient transition structure that effectively alleviates the problem of interface stress concentration. The thickness is precisely controlled within the range of 0.005μm-0.5μm, ensuring that the interface reinforcement layer can effectively transfer stress without excessively increasing the overall thickness, achieving the optimal balance between flexibility and mechanical strength.
[0022] 3. The functional adhesive layer of this invention is a composite of modified polyvinylidene fluoride (PVDF) and specific nanofillers. The modified PVDF contains active functional groups that can form chemical bonds with the metal oxide interface reinforcement layer. The addition of nanofillers further improves the mechanical properties and thermal stability of the adhesive layer, enabling the composite current collector to maintain excellent interfacial bonding performance over a wide temperature range. The thickness is controlled within the range of 0.1 μm to 5 μm, ensuring sufficient bonding strength while avoiding excessive increase in thickness and internal resistance.
[0023] 4. In the preparation method of the present invention, the microstructure of the interface is precisely controlled through the synergistic effect of multiple steps such as laser microstructure processing, atomic layer deposition, and plasma treatment, thereby maximizing the interfacial bonding force and ensuring production efficiency and product consistency.
[0024] 5. The composite current collector of the present invention abandons the traditional polymer base film layer, is thinner, improves the energy density of the battery, and avoids the wrinkling problem caused by the polymer base film layer, thereby improving the product yield.
[0025] 6. The preparation process of the present invention processes both sides of the first release film simultaneously, and two rolls of composite current collector can be produced in one process, which improves production efficiency and reduces production costs. Attached Figure Description
[0026] Figure 1This is a schematic cross-sectional view of a composite current collector with high interfacial bonding strength provided in an embodiment of the present invention. In this diagram, 1 is the first metal layer, 2 is the interface reinforcement layer, 3 is the functional adhesive layer, 4 is the second metal layer, 5 is the micro / nano trench structure, and 6 is the micro / nano protrusion structure. Detailed Implementation
[0027] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.
[0028] The present invention provides a composite current collector with high interfacial bonding force, which abandons the polymer material base film layer in traditional composite current collectors and adopts an innovative "first metal layer - interface reinforcement layer - functional adhesive layer - second metal layer" structure. Through the synergistic effect of micro-nano structure design, interface reinforcement layer and functional adhesive layer, the interfacial bonding force is significantly improved.
[0029] In some embodiments, a composite current collector with high interfacial bonding strength comprises, in the thickness direction, a first metal layer, an interface reinforcement layer, a functional adhesive layer, and a second metal layer, wherein micro-nano interlocking structures are formed between the first metal layer and the interface reinforcement layer, and between the functional adhesive layer and the second metal layer; the interface reinforcement layer is composed of metal oxide modified with nanoparticles, and has a thickness of 0.005 μm-0.5 μm; the functional adhesive layer is composed of modified polyvinylidene fluoride and nanofillers, and has a thickness of 0.1 μm-5 μm; the thicknesses of the first metal layer and the second metal layer are 0.01 μm-3 μm, respectively.
[0030] This four-layer structure design abandons the traditional sandwich structure of "metal layer-polymer base film layer-metal layer". By innovatively introducing an interface reinforcement layer and a functional adhesive layer, it solves the technical problem of insufficient interfacial bonding between the polymer base film layer and the metal layer. The formation of the micro-nano interlocking structure increases the interfacial contact area by 300%-500%, and significantly improves the interfacial bonding strength through mechanical interlocking. This effectively prevents the metal layer from falling off due to interfacial stress during battery charge and discharge cycles, solving the fundamental problems of poor interfacial stability and short cycle life of composite current collectors in existing technologies.
[0031] The thickness range of the interface reinforcement layer was determined through extensive experimental optimization. An interface reinforcement layer with a thickness range of 0.005μm-0.5μm can effectively transfer interface stress without excessively increasing the overall thickness, achieving the best balance between interface bonding strength and product flexibility, and solving the technical problem of microcracks caused by interface stress concentration in the prior art.
[0032] The thickness design of the functional adhesive layer is based on a balance between interfacial bonding strength and battery internal resistance. The thickness range of 0.1μm-5μm ensures that the functional adhesive layer provides high interfacial bonding strength while maintaining good ion conduction performance, thus solving the contradiction in the prior art where excessively thick adhesive layers lead to decreased battery performance, while excessively thin layers lead to insufficient interfacial bonding.
[0033] The design of the metal layer thickness range is based on a comprehensive consideration of conductivity, mechanical strength and energy density. The metal layer with a thickness range of 0.01μm-3μm ensures good conductivity while significantly reducing the weight of the current collector, thereby increasing the battery energy density by 15%-25%. This solves the technical problems in the prior art where excessively thick metal layers lead to low energy density and excessively thin metal layers lead to easy breakage.
[0034] See appendix Figure 1 As shown, the high interfacial bonding composite current collector of the present invention comprises, in the thickness direction, a first metal layer 1, an interface reinforcement layer 2, a functional adhesive layer 3, and a second metal layer 4. The surface of the first metal layer 1 has a micro-nano trench structure 5, and the surface of the second metal layer 4 has a micro-nano protrusion structure 6. The interface reinforcement layer 2 fills the micro-nano trench structure 5 and forms a mechanical interlock with the first metal layer 1; the functional adhesive layer 3 forms a mechanical interlock with the micro-nano protrusion structure 6, and simultaneously forms a chemical bond with the interface reinforcement layer 2.
[0035] The first metal layer 1 and the second metal layer 4 are made of metal or metal alloy, specifically selected from one or more of aluminum, copper, nickel, titanium, silver, or their alloys. The thickness of both the first metal layer 1 and the second metal layer 4 is 0.01 μm to 3 μm, preferably 0.1 μm to 1.5 μm. The first metal layer 1 and the second metal layer 4 can be made of the same material, for example, both being copper; or they can be different materials, for example, the first metal layer 1 is copper and the second metal layer 4 is aluminum.
[0036] The micro-nano trench structure 5 on the surface of the first metal layer 1 has a depth of 0.005 μm-0.1 μm, a width of 0.01 μm-0.5 μm, and a trench density of 50-500 trenches / μm. 2 The depth-to-width ratio of the micro-nano trench structure 5 is 1:2-1:10, preferably 1:5. This micro-nano structure design increases the contact area between the first metal layer 1 and the interface reinforcement layer 2, forming a mechanical interlock and significantly improving the interfacial bonding force.
[0037] The micro / nano protrusions 6 on the surface of the second metal layer 4 have a height of 0.005 μm-0.1 μm, a diameter of 0.01 μm-0.5 μm, and a protrusion density of 50-500 per μm. 2The height-to-diameter ratio of the micro / nano protrusion structure 6 is 1:2 to 1:10, preferably 1:5. This micro / nano structure design increases the contact area between the second metal layer 4 and the functional adhesive layer 3, forming a mechanical interlock and significantly improving the interfacial bonding force.
[0038] The interface reinforcement layer 2 is composed of nanoparticle-modified metal oxide with a thickness of 0.005 μm-0.5 μm, preferably 0.01 μm-0.1 μm. The metal oxide can be selected from one or more of alumina, titanium dioxide, or silicon oxide. The nanoparticles are one or more of silicon dioxide, alumina, or zirconium oxide, with a particle size of 5 nm-50 nm, and are added at 0.1%-5% of the total mass of the metal oxide, preferably 0.5%-2%. The nanoparticle modification of the interface reinforcement layer 2 gives it higher mechanical strength and better interfacial compatibility, effectively alleviating the problem of interfacial stress concentration.
[0039] The functional adhesive layer 3 is composed of modified polyvinylidene fluoride (PVDF) and nanofillers, with a thickness of 0.1 μm-5 μm, preferably 0.5 μm-2 μm. The modified PVDF is carboxylated or hydroxylated PVDF, wherein the carboxyl or hydroxyl content is 0.1%-5%, preferably 0.5%-2%. The nanofillers are one or more of carbon nanotubes, graphene, or boron nitride, and the addition amount is 0.01%-2% of the total mass of the adhesive, preferably 0.05%-1%. The active functional groups in the functional adhesive layer 3 can form chemical bonds with the interface reinforcement layer 2, and the addition of nanofillers improves the mechanical properties and thermal stability of the adhesive layer.
[0040] The present invention also provides a method for preparing the above-mentioned composite current collector with high interfacial bonding strength, comprising the following steps: S1. A first metal layer is deposited on both sides of the first release film by physical vapor deposition, and the surface of the first metal layer is subjected to laser microstructure treatment to form a micro-nano trench structure.
[0041] Physical vapor deposition can be selected from at least one of evaporation and sputtering; evaporation can be selected from at least one of vacuum evaporation, thermal evaporation, and electron beam evaporation; sputtering is preferably magnetron sputtering. The thickness of the first metal layer is 0.01 μm-3 μm, preferably 0.1 μm-1.5 μm.
[0042] The parameters for laser microstructure processing are: laser wavelength 266nm-1064nm, pulse width 10ps-100ns, and energy density 0.1J / cm². 2 -5J / cm 2 The scanning speed is 50 mm / s-500 mm / s, and the scanning spacing is 5 μm-50 μm. Laser microstructure processing can be performed in a vacuum or inert gas environment, and the surface roughness Ra after processing is 0.01 μm-0.5 μm.
[0043] The thickness of the first release film is 0.1μm-100μm, preferably 5μm-50μm; the release force of the first release film is 1gf / 25mm-25gf / 25mm, preferably 5gf / 25mm-15gf / 25mm. The first release film can be selected from materials such as PET, PI, and PP.
[0044] S2. An interface enhancement layer is formed on the surface of the first metal layer by atomic layer deposition, and the interface enhancement layer is subjected to plasma treatment.
[0045] The process parameters for forming the interface reinforcement layer by atomic layer deposition are as follows: deposition temperature 80℃-200℃, precursor is trimethylaluminum, titanium tetrachloride, or tetraethoxysilane, reaction chamber pressure 10Pa-100Pa, pulse time 0.01s-1s, purge time 1s-10s, and number of cycles 5-100. The thickness of the interface reinforcement layer is 0.005μm-0.5μm, preferably 0.01μm-0.1μm.
[0046] The parameters for plasma treatment are: oxygen flow rate 10-100 sccm, power 50W-500W, treatment time 10-120s, and treatment distance 5mm-20mm. Plasma treatment can improve the activity of the interface reinforcement layer surface, which is beneficial for subsequent bonding with functional adhesive layers.
[0047] S3. A functional adhesive layer is coated on the interface reinforcement layer to form a first semi-finished product comprising, in sequence, a functional adhesive layer, an interface reinforcement layer, a first metal layer, a first release film, a first metal layer, an interface reinforcement layer, and a functional adhesive layer.
[0048] The functional adhesive layer can be applied using one or more of the following methods: slot coating, doctor blade coating, micro-groove coating, screen roller coating, spraying, coating, transfer printing, lamination, film application, extrusion lamination, and surface sizing. The thickness of the functional adhesive layer is 0.1μm-5μm, preferably 0.5μm-2μm.
[0049] The formulation of the functional adhesive layer is as follows: 80%-99.99% modified polyvinylidene fluoride, 0.01%-2% nanofiller, and 0%-19.99% solvent. The modified polyvinylidene fluoride is carboxylated or hydroxylated polyvinylidene fluoride; the nanofiller is carbon nanotubes, graphene, or boron nitride; and the solvent is one or more of N-methylpyrrolidone, dimethylformamide, or dimethylacetamide.
[0050] S4. Apply the second release film to both sides of the first semi-finished product to form the second semi-finished product.
[0051] The thickness of the second release film is 0.1μm-100μm, preferably 5μm-50μm; the release force of the second release film is 1gf / 25mm-25gf / 25mm, preferably 5gf / 25mm-15gf / 25mm. The second release film can be selected from materials such as PET, PI, PP, etc., and can be the same as or different from the first release film.
[0052] S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, perform corona treatment on the peeled surface of the second release film, and deposit a second metal layer on the surface of the functional adhesive layer by physical vapor deposition, forming a micro-nano protrusion structure on the surface of the second metal layer.
[0053] The parameters for corona treatment are: treatment power 50W-500W, treatment speed 1m / min-50m / min, and electrode spacing 5mm-20mm. Corona treatment can increase the surface energy of the functional adhesive layer, which is beneficial for the subsequent deposition of the metal layer.
[0054] The parameters for depositing the second metal layer using physical vapor deposition are similar to those in S1, but micro / nano protrusion structures are formed on the surface of the second metal layer by adjusting the process parameters. The formation of the micro / nano protrusion structures can be achieved by controlling parameters such as deposition rate, substrate temperature, and gas flow rate. The thickness of the second metal layer is 0.01 μm-3 μm, preferably 0.1 μm-1.5 μm.
[0055] S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0056] The peeling process can be achieved through a winding system: the composite current collectors on both sides of the first release film are wound onto two take-up rollers respectively, and the first release film is wound onto another take-up roller. By controlling the winding speed and tension, the composite current collectors and the first release film can be peeled off without damage.
[0057] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0058] Example 1 This embodiment provides a composite current collector with high interfacial bonding strength, which is prepared through the following steps: S1. Copper is deposited on both sides of the first release film by magnetron sputtering to form a first metal layer, wherein the thickness of the first metal layer is 1μm. The first release film is made of PET material, with a thickness of 25μm and a release force of 10gf / 25mm.
[0059] Subsequently, the surface of the first metal layer was subjected to laser microstructure processing with the following parameters: laser wavelength 355nm, pulse width 30ps, and energy density 1.5J / cm². 2The scanning speed was 100 mm / s, and the scanning spacing was 10 μm. After processing, a trench structure with a depth of approximately 0.05 μm and a width of approximately 0.25 μm was formed on the surface of the first metal layer, with a trench density of approximately 200 trenches / μm. 2 The surface roughness Ra is 0.2 μm.
[0060] S2. An interface reinforcement layer is formed on the surface of the first metal layer by atomic layer deposition. The process parameters are: deposition temperature 120℃, precursor is trimethylaluminum, reaction chamber pressure 50Pa, pulse time 0.1s, purge time 5s, and number of cycles 20. The interface reinforcement layer has a thickness of approximately 0.05μm and is composed of nanoparticle-modified alumina, of which alumina accounts for 98% and silica nanoparticles (particle size 20nm) account for 2%.
[0061] The interface enhancement layer was then subjected to plasma treatment with the following parameters: oxygen flow rate 50 sccm, power 200 W, treatment time 60 s, and treatment distance 10 mm.
[0062] S3. A functional adhesive layer is coated onto the interface reinforcement layer using a slit coating method, forming a first semi-finished product comprising, in sequence, a functional adhesive layer, an interface reinforcement layer, a first metal layer, a first release film, a first metal layer, an interface reinforcement layer, and a functional adhesive layer. The formulation of the functional adhesive layer is: 98.5% carboxylated polyvinylidene fluoride (carboxyl content 1.5%), 0.5% carbon nanotubes (diameter 10nm, length 1μm), 1% N-methylpyrrolidone, with a solid content of 35%. The thickness of the functional adhesive layer is 1μm.
[0063] S4. Apply a second release film to both sides of the first semi-finished product to form the second semi-finished product. The second release film is made of PET material, with a thickness of 25μm and a release force of 10gf / 25mm.
[0064] S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, and subject the peeled surface to corona treatment with the following parameters: treatment power 200W, treatment speed 10m / min, and electrode spacing 10mm. Simultaneously, deposit copper onto the surface of the functional adhesive layer using magnetron sputtering to form a second metal layer with a thickness of 1μm. This is achieved by controlling the magnetron sputtering parameters (power density 1.5W / cm³). 2 (Argon flow rate 30 sccm, substrate temperature 80℃) to form a protrusion structure on the surface of the second metal layer with a height of approximately 0.05 μm and a diameter of approximately 0.25 μm, with a protrusion density of approximately 200 protrusions / μm. 2 .
[0065] S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0066] Example 2 S1. Aluminum is deposited on both sides of the first release film by electron beam evaporation to form a first metal layer, wherein the thickness of the first metal layer is 0.5μm. The first release film is made of PI material, with a thickness of 10μm and a release force of 5gf / 25mm.
[0067] Subsequently, the surface of the first metal layer was subjected to laser microstructure processing with the following parameters: laser wavelength 532nm, pulse width 50ps, and energy density 0.8J / cm². 2 The scanning speed was 150 mm / s, and the scanning spacing was 8 μm. After processing, a trench structure with a depth of approximately 0.03 μm and a width of approximately 0.15 μm was formed on the surface of the first metal layer, with a trench density of approximately 300 trenches / μm. 2 The surface roughness Ra is 0.15 μm.
[0068] S2. An interface reinforcement layer is formed on the surface of the first metal layer by atomic layer deposition. The process parameters are: deposition temperature 100℃, precursor is tetraethoxysilane, reaction chamber pressure 30Pa, pulse time 0.05s, purge time 3s, and number of cycles 15. The interface reinforcement layer has a thickness of approximately 0.03μm and is composed of nanoparticle-modified silicon dioxide, of which silicon dioxide accounts for 99% and alumina nanoparticles (particle size 10nm) account for 1%.
[0069] The interface enhancement layer was then subjected to plasma treatment with the following parameters: oxygen flow rate 30 sccm, power 150 W, treatment time 40 s, and treatment distance 8 mm.
[0070] S3. A functional adhesive layer is coated onto the interface reinforcement layer using a micro-recessed coating method to form the first semi-finished product. The formulation of the functional adhesive layer is: 99.2% hydroxylated polyvinylidene fluoride (hydroxyl content 1%), 0.3% graphene (monolayer, thickness 0.8nm), 0.5% dimethylacetamide, with a solid content of 40%. The thickness of the functional adhesive layer is 0.8μm.
[0071] S4. Apply a second release film to both sides of the first semi-finished product to form the second semi-finished product. The second release film is made of PI material, with a thickness of 10μm and a release force of 5gf / 25mm.
[0072] S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, and subject the peeled surface to corona treatment with the following parameters: treatment power 150W, treatment speed 8m / min, and electrode spacing 8mm. Simultaneously, deposit aluminum onto the surface of the functional adhesive layer using electron beam evaporation to form a second metal layer with a thickness of 0.5μm. This is achieved by controlling the evaporation parameters (evaporation rate 0.5nm / s, vacuum degree 5×10⁻⁶). - (³Pa), causing a protrusion structure with a height of approximately 0.03μm and a diameter of approximately 0.15μm to be formed on the surface of the second metal layer, with a protrusion density of approximately 300 protrusions / μm.2 .
[0073] S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0074] Example 3 S1. A copper-nickel alloy (Cu:Ni=9:1) is deposited on both sides of the first release film by magnetron sputtering to form a first metal layer, wherein the thickness of the first metal layer is 1.2μm. The first release film is made of PP material, with a thickness of 50μm and a release force of 15gf / 25mm.
[0075] Subsequently, the surface of the first metal layer was subjected to laser microstructure processing with the following parameters: laser wavelength 1064 nm, pulse width 80 ns, and energy density 3 J / cm². 2 The scanning speed was 80 mm / s, and the scanning spacing was 20 μm. After processing, a trench structure with a depth of approximately 0.08 μm and a width of approximately 0.4 μm was formed on the surface of the first metal layer, with a trench density of approximately 150 trenches / μm. 2 The surface roughness Ra is 0.25 μm.
[0076] S2. An interface reinforcement layer is formed on the surface of the first metal layer using atomic layer deposition (ALD). The process parameters are: deposition temperature 150℃, precursor titanium tetrachloride, reaction chamber pressure 80 Pa, pulse time 0.2 s, purge time 8 s, and cycle count 30. The interface reinforcement layer has a thickness of approximately 0.08 μm and is composed of nanoparticle-modified titanium oxide, of which titanium oxide accounts for 97% and zirconium oxide nanoparticles (30 nm in diameter) account for 3%.
[0077] The interface enhancement layer was then subjected to plasma treatment with the following parameters: oxygen flow rate 80 sccm, power 300 W, treatment time 90 s, and treatment distance 15 mm.
[0078] S3. A functional adhesive layer is coated onto the interface reinforcement layer by spraying to form the first semi-finished product. The formulation of the functional adhesive layer is: 97% carboxylated polyvinylidene fluoride (carboxyl content 2%), 1.5% boron nitride (thickness 1nm, diameter 50nm), 1.5% N-methylpyrrolidone, and a solid content of 30%. The thickness of the functional adhesive layer is 1.2μm.
[0079] S4. Apply a second release film to both sides of the first semi-finished product to form the second semi-finished product. The second release film is made of PP material, with a thickness of 50μm and a release force of 15gf / 25mm.
[0080] S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, and subject the peeled surface to corona treatment with the following parameters: treatment power 300W, treatment speed 12m / min, and electrode spacing 15mm. Simultaneously, deposit a copper-nickel alloy (Cu:Ni=9:1) onto the surface of the functional adhesive layer using magnetron sputtering to form a second metal layer with a thickness of 1.2μm. This is achieved by controlling the magnetron sputtering parameters (power density 2W / cm³). 2 (Argon flow rate 40 sccm, substrate temperature 100℃) to form a protrusion structure on the surface of the second metal layer with a height of approximately 0.08 μm and a diameter of approximately 0.4 μm, with a protrusion density of approximately 150 protrusions / μm. 2 .
[0081] S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0082] Example 4 S1. Aluminum is deposited on both sides of the first release film by thermal evaporation to form a first metal layer, wherein the thickness of the first metal layer is 0.2μm. The first release film is made of PET material, with a thickness of 5μm and a release force of 3gf / 25mm.
[0083] Subsequently, the surface of the first metal layer was subjected to laser microstructure processing with the following parameters: laser wavelength 266 nm, pulse width 10 ps, and energy density 0.5 J / cm². 2 The scanning speed was 200 mm / s, and the scanning spacing was 5 μm. After processing, a trench structure with a depth of approximately 0.01 μm and a width of approximately 0.05 μm was formed on the surface of the first metal layer, with a trench density of approximately 500 trenches / μm. 2 The surface roughness Ra is 0.05 μm.
[0084] S2. An interface reinforcement layer is formed on the surface of the first metal layer by atomic layer deposition. The process parameters are: deposition temperature 80℃, precursor is trimethylaluminum, reaction chamber pressure 10Pa, pulse time 0.01s, purge time 1s, and number of cycles 5. The interface reinforcement layer has a thickness of approximately 0.01μm and is composed of nanoparticle-modified alumina, of which alumina accounts for 99.5% and silica nanoparticles (particle size 5nm) account for 0.5%.
[0085] The interface enhancement layer was then subjected to plasma treatment with the following parameters: oxygen flow rate 10 sccm, power 50 W, treatment time 10 s, and treatment distance 5 mm.
[0086] S3. A functional adhesive layer is coated onto the interface reinforcement layer using a screen roller coating method to form the first semi-finished product. The formulation of the functional adhesive layer is as follows: 99.8% hydroxylated polyvinylidene fluoride (hydroxyl content 0.5%), 0.1% carbon nanotubes (diameter 5nm, length 0.5μm), 0.1% dimethylformamide, and a solid content of 50%. The thickness of the functional adhesive layer is 0.5μm.
[0087] S4. Apply a second release film to both sides of the first semi-finished product to form the second semi-finished product. The second release film is made of PET material, with a thickness of 5μm and a release force of 3gf / 25mm.
[0088] S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, and subject the peeled surface to corona treatment with the following parameters: treatment power 50W, treatment speed 5m / min, and electrode spacing 5mm. Simultaneously, aluminum is thermally evaporated onto the surface of the functional adhesive layer to form a second metal layer with a thickness of 0.2μm. This is achieved by controlling the evaporation parameters (evaporation rate 0.2nm / s, vacuum degree 1×10⁻⁶). - (³Pa), causing a protrusion structure with a height of approximately 0.01μm and a diameter of approximately 0.05μm to be formed on the surface of the second metal layer, with a protrusion density of approximately 500 protrusions / μm. 2 .
[0089] S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0090] Example 5 S1. Copper is deposited on both sides of the first release film by magnetron sputtering to form a first metal layer, wherein the thickness of the first metal layer is 1.5μm. The first release film is made of PET material, with a thickness of 30μm and a release force of 12gf / 25mm.
[0091] Subsequently, the surface of the first metal layer was subjected to laser microstructure processing with the following parameters: laser wavelength 355nm, pulse width 40ps, and energy density 2J / cm². 2 The scanning speed was 120 mm / s, and the scanning spacing was 12 μm. After processing, a trench structure with a depth of approximately 0.06 μm and a width of approximately 0.3 μm was formed on the surface of the first metal layer, with a trench density of approximately 180 trenches / μm. 2 The surface roughness Ra is 0.22 μm.
[0092] S2. An interface reinforcement layer is formed on the surface of the first metal layer using atomic layer deposition (ALD). The process parameters are: deposition temperature 130℃, trimethylaluminum as the precursor, reaction chamber pressure 60 Pa, pulse time 0.12 s, purge time 6 s, and 25 cycles. The interface reinforcement layer has a thickness of approximately 0.06 μm and is composed of nanoparticle-modified alumina, of which alumina accounts for 97.5% and silica nanoparticles (25 nm in diameter) account for 2.5%.
[0093] The interface enhancement layer was then subjected to plasma treatment with the following parameters: oxygen flow rate 60 sccm, power 250 W, treatment time 70 s, and treatment distance 12 mm.
[0094] S3. A functional adhesive layer is coated onto the interface reinforcement layer using a doctor blade coating method to form the first semi-finished product. The formulation of the functional adhesive layer is: 98% carboxylated polyvinylidene fluoride (carboxyl content 1.8%), 1% graphene (monolayer, thickness 0.8nm), 1% N-methylpyrrolidone, with a solid content of 32%. The thickness of the functional adhesive layer is 1.5μm. The adhesive layer is then cured and aged, with a curing temperature of 90℃ for 90s and an aging temperature of 50℃ for 2 days.
[0095] S4. Apply a second release film to both sides of the first semi-finished product to form the second semi-finished product. The second release film is made of PET material, with a thickness of 30μm and a release force of 12gf / 25mm.
[0096] S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, and subject the peeled surface to corona treatment with the following parameters: treatment power 250W, treatment speed 11m / min, and electrode spacing 12mm. Simultaneously, copper is deposited on the surface of the functional adhesive layer by magnetron sputtering to form a second metal layer with a thickness of 1.5μm. This is achieved by controlling the magnetron sputtering parameters (power density 1.8W / cm³). 2 With an argon flow rate of 35 sccm and a substrate temperature of 90°C, a raised structure with a height of approximately 0.06 μm and a diameter of approximately 0.3 μm is formed on the surface of the second metal layer, with a raised density of approximately 180 protrusions / μm. 2 .
[0097] S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0098] Example 6 S1. Aluminum is deposited on both sides of the first release film by vacuum evaporation to form a first metal layer, wherein the thickness of the first metal layer is 0.8μm. The first release film is made of PI material, with a thickness of 20μm and a release force of 8gf / 25mm.
[0099] Subsequently, the surface of the first metal layer was subjected to laser microstructure processing with the following parameters: laser wavelength 532nm, pulse width 60ps, and energy density 1J / cm². 2 The scanning speed was 180 mm / s, and the scanning spacing was 10 μm. After processing, a trench structure with a depth of approximately 0.04 μm and a width of approximately 0.2 μm was formed on the surface of the first metal layer, with a trench density of approximately 250 trenches / μm. 2 The surface roughness Ra is 0.18 μm.
[0100] S2. An interface reinforcement layer is formed on the surface of the first metal layer using atomic layer deposition (ALD). The process parameters are: deposition temperature 110℃, precursor tetraethoxysilane, reaction chamber pressure 40 Pa, pulse time 0.08 s, purge time 4 s, and cycle count 20. The interface reinforcement layer has a thickness of approximately 0.04 μm and is composed of nanoparticle-modified silicon dioxide, of which silicon dioxide accounts for 98.5% and alumina nanoparticles (15 nm in diameter) account for 1.5%.
[0101] The interface enhancement layer was then subjected to plasma treatment with the following parameters: oxygen flow rate 40 sccm, power 180 W, treatment time 50 s, and treatment distance 10 mm.
[0102] S3. A functional adhesive layer is coated onto the interface reinforcement layer by transfer printing to form the first semi-finished product. The formulation of the functional adhesive layer is as follows: 98.8% hydroxylated polyvinylidene fluoride (hydroxyl content 1.2%), 0.7% boron nitride (thickness 1.2nm, diameter 60nm), 0.5% dimethylacetamide, and a solid content of 45%. The thickness of the functional adhesive layer is 1μm.
[0103] S4. Apply a second release film to both sides of the first semi-finished product to form the second semi-finished product. The second release film is made of PI material, with a thickness of 20μm and a release force of 8gf / 25mm.
[0104] S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, and subject the peeled surface to corona treatment with the following parameters: treatment power 180W, treatment speed 9m / min, and electrode spacing 10mm. Simultaneously, deposit aluminum onto the surface of the functional adhesive layer via vacuum evaporation to form a second metal layer with a thickness of 0.8μm. This is achieved by controlling the evaporation parameters (evaporation rate 0.3nm / s, vacuum degree 3×10⁻⁶). - (³Pa), forming a protrusion structure with a height of approximately 0.04μm and a diameter of approximately 0.2μm on the surface of the second metal layer, with a protrusion density of approximately 250 protrusions / μm. 2 .
[0105] S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
[0106] Comparative Example 1 Copper was deposited on both sides of a 4.5 μm thick PP film using magnetron sputtering and electroplating, forming metal layers on both sides of the PP film, each with a thickness of 1 μm. First, the metal layer was deposited to a thickness of 0.05 μm using magnetron sputtering, and then to a thickness of 1 μm using electroplating.
[0107] Comparative Example 2 Aluminum is deposited on both sides of a 4.5μm thick PP film by vacuum evaporation, forming a metal layer on both sides of the PP film. The thickness of the metal layer on both sides of the PP film is 1μm.
[0108] Comparative Example 3 Copper was deposited on both sides of a 6 μm thick PET film using magnetron sputtering and electroplating, forming metal layers on both sides of the PET film, each with a thickness of 1 μm. First, the metal layer was deposited to a thickness of 0.05 μm using magnetron sputtering, and then to a thickness of 1 μm using electroplating.
[0109] Comparative Example 4 Aluminum is deposited on both sides of a 6μm thick PET film by vacuum evaporation, forming a metal layer on both sides of the PET film. The thickness of the metal layer on both sides of the PET film is 1μm.
[0110] Comparative Example 5 The composite current collector described in CN117832502A includes a first metal layer, an adhesive layer, and a second metal layer, with the first and second metal layers respectively disposed on opposite sides of the adhesive layer. For specific preparation methods, refer to Example 1 of CN117832502A.
[0111] Performance testing 1. Peel force test Peel force tests were conducted on the composite current collectors prepared in Examples 1-6 and Comparative Examples 1-5: A tensile testing machine was used to test the peel force between the interface reinforcement layer and the first metal layer, and the peel force between the functional adhesive layer and the second metal layer. Test samples with dimensions of 15×100mm were taken. Adhesive tape was applied to a stainless steel plate, and the sample was then evenly applied to double-sided adhesive. A 2kg standard small pressure roller was used to press the sample back and forth twice. The tape was then adhered to the sample surface, and the sample was pressed back and forth twice again using the same 2kg standard small pressure roller. The pressed sample was then subjected to a 180° stretch at a speed of 100mm / min on the tensile testing machine. The maximum value was recorded. The peel force test results are shown in Table 1. Table 1
[0112] As can be seen from the data in Table 1, the total interfacial peel strength of Examples 1-6 is significantly higher than that of Comparative Examples 1-5. Among them, Examples 3 and 6 have the highest total interfacial peel strength, reaching 445 N / m and 440 N / m respectively, which are about 19.3% and 18.0% higher than that of Comparative Example 5 (CN117832502A technology). This indicates that the present invention significantly improves the interfacial bonding strength through the synergistic effect of micro-nano structure design, interface reinforcement layer and functional adhesive layer.
[0113] 2. Cyclic performance test The composite current collectors prepared in Examples 1-6 and Comparative Examples 1-5 were used to prepare lithium-ion batteries through the following steps: Ternary material NCM811 was selected as the positive electrode. It was mixed with an adhesive (polyvinylidene fluoride, PVDF) and a conductive agent (Super P) in NMP solvent at a mass ratio of 96:2:2 to prepare a positive electrode slurry. The positive electrode slurry was then coated onto an aluminum-based composite current collector (Examples 3 and 6, or Comparative Examples 2, 4, and 5), with an areal density of 20 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 120°C to obtain the positive electrode sheet.
[0114] Artificial graphite was selected as the negative electrode material. It was mixed with a binder (carboxymethyl cellulose, CMC) and a conductive agent (SuperP) in deionized water at a mass ratio of 95:2.5:2.5 to prepare a negative electrode slurry. This slurry was then coated onto a copper-based composite current collector (Examples 1, 2, 5 or Comparative Examples 1, 3, 5), with an areal density of 18 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 100°C to obtain the negative electrode sheet.
[0115] The above-mentioned positive electrode, negative electrode, separator (Celgard 2325) and lithium-ion electrolyte are assembled into a 2032 coin cell.
[0116] Using the composite current collector prepared in Comparative Example 5 as a control, the cycle performance of the above-mentioned lithium-ion battery was tested according to the test methods in GB / T 31484-2015 "Cycle Life Requirements and Test Methods for Power Batteries for Electric Vehicles". Test conditions: At 25℃, 1C constant current charging to 4.2V, followed by constant voltage charging to 0.05C, resting for 10 min, and 1C constant current discharging to 3.0V. After 500 cycles, the capacity retention rate was recorded. The test results are shown in Table 2. Table 2
[0117] As can be seen from the data in Table 2, the batteries assembled using the composite current collector prepared according to the embodiments of the present invention exhibit significantly higher capacity retention after 500 cycles compared to the comparative examples. Specifically, experimental examples 2-3 achieve a retention rate of 90.2%, approximately 4.5 percentage points higher than comparative example 5. The capacity decay rate is also significantly lower than that of the comparative examples, indicating that the composite current collector of the present invention has better interfacial stability and effectively reduces capacity decay caused by interfacial separation during cycling.
[0118] 3. Ratio Performance The composite current collectors prepared in Examples 1-6 and Comparative Examples 1-5 were used to prepare lithium-ion batteries through the following steps: Lithium iron phosphate (LFP) was selected as the positive electrode. It was mixed with an adhesive (polyvinylidene fluoride, PVDF) and a conductive agent (SuperP) in NMP solvent at a mass ratio of 96:2:2 to prepare a positive electrode slurry. The positive electrode slurry was then coated onto an aluminum-based composite current collector (Examples 3 and 6, or Comparative Examples 2, 4, and 5), with an areal density of 22 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 120°C to obtain the positive electrode sheet.
[0119] Silicon-carbon composite material was selected as the negative electrode material. It was mixed with an adhesive (carboxymethyl cellulose, CMC) and a conductive agent (Super P) in deionized water at a mass ratio of 90:5:5 to prepare a negative electrode slurry. The negative electrode slurry was then coated onto a copper-based composite current collector (Examples 1, 2, 5 or Comparative Examples 1, 3, 5), with an areal density of 20 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 100°C to obtain the negative electrode sheet.
[0120] The above-mentioned positive electrode, negative electrode, separator (Celgard 2325) and lithium-ion electrolyte are assembled into a soft-pack battery (50Ah).
[0121] The above batteries were subjected to rate performance tests: At 25℃, they were charged at a constant current of 0.5C to 3.65V, then switched to constant voltage charging to 0.05C, allowed to stand for 10 minutes, and then discharged at different rates (0.5C, 1C, 2C, 3C, 5C) at a constant current to 2.5V. The discharge capacity was recorded. The test results are shown in Table 3. Table 3
[0122] As can be seen from the data in Table 3, the batteries assembled using the composite current collector prepared according to the embodiments of the present invention exhibit better capacity retention under high-rate discharge conditions. Specifically, experimental examples 3-3 achieve a capacity retention of 95.6% at 5C discharge, approximately 5 percentage points higher than comparative example 5. This indicates that the high interfacial bonding composite current collector of the present invention can effectively reduce capacity loss caused by interfacial separation during high-rate charge and discharge, thereby improving the power performance of the battery.
[0123] 4. Needle prick test The composite current collectors prepared in Examples 1-6 and Comparative Examples 1-5 were used to prepare lithium-ion batteries through the following steps: A high-nickel ternary material, NCM9055, was selected as the positive electrode. It was mixed with an adhesive (polyvinylidene fluoride, PVDF) and a conductive agent (Super P) in NMP solvent at a mass ratio of 95:2.5:2.5 to prepare a positive electrode slurry. This slurry was then coated onto an aluminum-based composite current collector (Examples 3 and 6, or Comparative Examples 2, 4, and 5), with an areal density of 25 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 120°C to obtain the positive electrode sheet.
[0124] Silicon-carbon composite material was selected as the negative electrode material. It was mixed with an adhesive (carboxymethyl cellulose, CMC) and a conductive agent (Super P) in deionized water at a mass ratio of 85:7:8 to prepare a negative electrode slurry. The negative electrode slurry was then coated onto a copper-based composite current collector (Examples 1, 2, 5 or Comparative Examples 1, 3, 5), with an areal density of 22 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 100°C to obtain the negative electrode sheet.
[0125] The above-mentioned positive electrode, negative electrode, separator (Celgard 2325) and lithium-ion electrolyte (1mol / L LiPF6 in EC:DEC:DMC=1:1:1) are assembled into a soft-pack battery (30Ah).
[0126] The above-mentioned batteries were subjected to a needle penetration test. The test procedure was as follows: After the individual battery was fully charged, a Φ3mm high-temperature resistant steel needle (with a cone angle of 45° at the tip, and a smooth surface free of rust, oxide layer, and oil) was used to penetrate the battery at a speed of (25±5)mm / s, perpendicular to the battery plates. The penetration point should be close to the geometric center of the pierced surface. The steel needle remained in the battery for 1 hour. The needle penetration results are shown in Table 4. Table 4
[0127] As can be seen from the data in Table 4, the batteries assembled using the composite current collector prepared according to the embodiments of the present invention exhibit a smaller temperature rise during the nail penetration test. The highest temperature in experimental examples 4-3 was only 75°C, and no smoke was observed, indicating that the composite current collector of the present invention has better safety performance. This is attributed to the high interfacial bonding design of the present invention, which effectively prevents the separation of the metal layer and the adhesive layer during the nail penetration process, avoids the expansion of internal short circuits, and thus improves battery safety.
[0128] 5. Thermal stability test The composite current collectors prepared in Examples 1-6 and Comparative Examples 1-5 were used to prepare lithium-ion batteries through the following steps: Ternary material NCM811 was selected as the positive electrode. It was mixed with an adhesive (polyvinylidene fluoride, PVDF) and a conductive agent (Super P) in NMP solvent at a mass ratio of 96:2:2 to prepare a positive electrode slurry. The positive electrode slurry was then coated onto an aluminum-based composite current collector (Examples 3 and 6, or Comparative Examples 2, 4, and 5), with an areal density of 20 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 120°C to obtain the positive electrode sheet.
[0129] Artificial graphite was selected as the negative electrode material. It was mixed with a binder (carboxymethyl cellulose, CMC) and a conductive agent (SuperP) in deionized water at a mass ratio of 95:2.5:2.5 to prepare a negative electrode slurry. This slurry was then coated onto a copper-based composite current collector (Examples 1, 2, 5 or Comparative Examples 1, 3, 5), with an areal density of 18 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 100°C to obtain the negative electrode sheet.
[0130] The above-mentioned positive electrode, negative electrode, separator (Celgard 2325) and lithium-ion electrolyte (1mol / L LiPF6 in EC:DEC:DMC=1:1:1) are assembled into a 2032 coin cell.
[0131] Thermal stability tests were performed on the above batteries: The batteries were charged at a constant current of 0.5C to 4.2V, then switched to constant voltage charging to 0.05C, allowed to stand for 10 minutes, and then placed in a heating chamber. The batteries were heated from 25℃ to 300℃ at a heating rate of 5℃ / min, and the temperature and voltage changes were recorded. The test results are shown in Table 5. Table 5
[0132] As can be seen from the data in Table 5, the battery assembled using the composite current collector prepared according to the embodiments of the present invention has a higher thermal runaway initiation temperature (185℃ in Experimental Example 5-3), a lower thermal runaway peak temperature (230℃ in Experimental Example 5-3), and a longer thermal runaway time (125s in Experimental Example 5-3), indicating that the composite current collector of the present invention has better thermal stability. This is attributed to the high interfacial bonding design of the present invention, which effectively delays interfacial separation and short-circuit propagation during thermal runaway, thereby improving the safety performance of the battery.
[0133] 6. Low-temperature performance test The composite current collectors prepared in Examples 1-6 and Comparative Examples 1-5 were used to prepare lithium-ion batteries through the following steps: Ternary material NCM811 was selected as the positive electrode. It was mixed with an adhesive (polyvinylidene fluoride, PVDF) and a conductive agent (Super P) in NMP solvent at a mass ratio of 96:2:2 to prepare a positive electrode slurry. The positive electrode slurry was then coated onto an aluminum-based composite current collector (Examples 3 and 6, or Comparative Examples 2, 4, and 5), with an areal density of 20 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 120°C to obtain the positive electrode sheet.
[0134] Artificial graphite was selected as the negative electrode material. It was mixed with a binder (carboxymethyl cellulose, CMC) and a conductive agent (SuperP) in deionized water at a mass ratio of 95:2.5:2.5 to prepare a negative electrode slurry. This slurry was then coated onto a copper-based composite current collector (Examples 1, 2, 5 or Comparative Examples 1, 3, 5), with an areal density of 18 mg / cm³. 2 Then, it is dried in a vacuum drying oven at 100°C to obtain the negative electrode sheet.
[0135] The above-mentioned positive electrode, negative electrode, separator (Celgard 2325) and lithium-ion electrolyte (1mol / L LiPF6 in EC:DEC:DMC=1:1:1) are assembled into a 2032 coin cell.
[0136] The batteries were subjected to low-temperature performance tests: At -20℃, they were charged at a constant current of 0.2C to 4.2V, then switched to constant voltage charging to 0.05C, allowed to stand for 10 minutes, and then discharged at a constant current of 0.2C to 3.0V. The discharge capacity was recorded. Simultaneously, the discharge capacity at 25℃ was tested as a benchmark to calculate the low-temperature capacity retention rate. The test results are shown in Table 6. Table 6
[0137] As can be seen from the data in Table 6, the batteries assembled using the composite current collector prepared according to the embodiments of the present invention exhibit better capacity retention at a low temperature of -20℃. Specifically, experimental examples 6-3 achieve 90.2%, which is approximately 2.3 percentage points higher than comparative example 5. This indicates that the high interfacial bonding composite current collector of the present invention can effectively reduce capacity loss caused by interfacial stress under low-temperature conditions, thereby improving the low-temperature performance of the battery.
[0138] As can be seen from the above embodiments and experimental data, the composite current collector with high interfacial bonding strength and its preparation method provided by the present invention have the following advantages: 1. Through the synergistic effect of micro-nano structure design on the surface of the metal layer, interface enhancement layer and functional adhesive layer, the interfacial bonding force is significantly improved, and the peel force is improved by about 18%-19% compared with the existing technology.
[0139] 2. The battery prepared using the composite current collector of the present invention has better cycle performance, with the capacity retention rate increasing by about 4.5 percentage points after 500 cycles.
[0140] 3. The composite current collector of the present invention effectively improves the rate performance of the battery, and increases the capacity retention rate by about 5 percentage points under 5C high-rate discharge conditions.
[0141] 4. The composite current collector of the present invention significantly improves the safety performance of the battery, with less temperature rise and no smoke in the nail penetration test.
[0142] 5. The composite current collector of the present invention improves the thermal stability of the battery, increases the thermal runaway initiation temperature by about 13°C, and reduces the thermal runaway peak temperature by about 20°C.
[0143] 6. The composite current collector of the present invention improves the low-temperature performance of the battery, and the capacity retention rate at -20°C is increased by about 2.3 percentage points.
[0144] In summary, the composite current collector with high interfacial bonding strength provided by this invention and its preparation method effectively solve the problem of insufficient interfacial bonding strength in existing composite current collectors through innovative structural design and preparation process. It has significant technological progress and practical value, and is suitable for the manufacture of high energy density and high safety lithium-ion batteries.
[0145] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A composite current collector with high interfacial bonding strength, characterized in that, From the thickness direction, it includes, in sequence: a first metal layer, an interface reinforcement layer, a functional adhesive layer, and a second metal layer; Micro-nano interlocking structures are formed between the first metal layer and the interface reinforcement layer, and between the functional adhesive layer and the second metal layer; the interface reinforcement layer is composed of metal oxide modified with nanoparticles, with a thickness of 0.005μm-0.5μm; the functional adhesive layer is composed of modified polyvinylidene fluoride and nanofillers, with a thickness of 0.1μm-5μm; the thicknesses of the first metal layer and the second metal layer are 0.01μm-3μm, respectively.
2. The composite current collector with high interfacial bonding strength according to claim 1, characterized in that, The materials of the first metal layer and the second metal layer are independently selected from one or more of aluminum, copper, nickel, titanium, silver or their alloys.
3. The composite current collector with high interfacial bonding strength according to claim 1, characterized in that, In the nanoparticle-modified metal oxide of the interface enhancement layer, the nanoparticles are one or more of silicon dioxide, aluminum oxide or zirconium oxide, with a particle size of 5nm-50nm, and the amount added is 0.1%-5% of the total mass of the metal oxide.
4. The composite current collector with high interfacial bonding strength according to claim 1, characterized in that, In the functional adhesive layer, the modified polyvinylidene fluoride is carboxylated polyvinylidene fluoride or hydroxylated polyvinylidene fluoride, and the nanofiller is one or more of carbon nanotubes, graphene or boron nitride, with an addition amount of 0.01%-2% of the total mass of the adhesive.
5. The composite current collector with high interfacial bonding strength according to claim 1, characterized in that, The micro / nano structure on the surface of the first metal layer consists of trenches with a depth of 0.005 μm-0.1 μm and a width of 0.01 μm-0.5 μm, with a trench density of 50-500 trenches / μm. 2 The micro / nano structure on the surface of the second metal layer consists of protrusions with a height of 0.005 μm-0.1 μm and a diameter of 0.01 μm-0.5 μm, with a protrusion density of 50-500 per μm. 2 .
6. The composite current collector with high interfacial bonding strength according to claim 1, characterized in that, The metal oxide in the interface enhancement layer is one or more of aluminum oxide, titanium oxide, or silicon oxide.
7. The composite current collector with high interfacial bonding strength according to any one of claims 1-6, characterized in that, The composite current collector is applied to the positive or negative electrode of a lithium-ion battery. When applied to the negative electrode, the first metal layer is copper or a copper alloy, and the second metal layer is copper or a copper alloy. When applied to the positive electrode, the first metal layer is aluminum or an aluminum alloy, and the second metal layer is aluminum or an aluminum alloy.
8. A method for preparing a composite current collector with high interfacial bonding strength, characterized in that, The method for preparing the composite current collector with high interfacial bonding strength according to any one of claims 1-6 comprises the following steps: S1. A first metal layer is deposited on both sides of the first release film by physical vapor deposition, and the surface of the first metal layer is subjected to laser microstructure treatment to form a micro-nano trench structure. S2. An interface reinforcement layer is formed on the surface of the first metal layer by atomic layer deposition, and the interface reinforcement layer is subjected to plasma treatment. S3. Coat the interface reinforcement layer with a functional adhesive layer to form a first semi-finished product comprising, in sequence, a functional adhesive layer, an interface reinforcement layer, a first metal layer, a first release film, a first metal layer, an interface reinforcement layer, and a functional adhesive layer. S4. Apply the second release film to both sides of the first semi-finished product to form the second semi-finished product; S5. Peel the second release film from the functional adhesive layer in the second semi-finished product, perform corona treatment on the peeling surface of the second release film, and deposit a second metal layer on the surface of the functional adhesive layer by physical vapor deposition, forming a micro-nano protrusion structure on the surface of the second metal layer. S6. Peel off the composite current collector and the first release film to obtain two rolls of composite current collector with high interfacial bonding strength.
9. The method for preparing a composite current collector with high interfacial bonding strength according to claim 8, characterized in that, The parameters for laser microstructure processing described in S1 are: laser wavelength 266nm-1064nm, pulse width 10ps-100ns, and energy density 0.1J / cm². 2 -5J / cm 2 The scanning speed is 50mm / s-500mm / s, and the scanning spacing is 5μm-50μm.
10. The method for preparing a composite current collector with high interfacial bonding strength according to claim 8, characterized in that, The process parameters for forming the interface enhancement layer by atomic layer deposition in S2 are as follows: deposition temperature 80℃-200℃, precursor is trimethylaluminum, titanium tetrachloride or tetraethoxysilane, reaction chamber pressure 10Pa-100Pa, pulse time 0.01s-1s, purging time 1s-10s, and number of cycles 5-100; the parameters for plasma treatment are as follows: oxygen flow rate 10sccm-100sccm, power 50W-500W, treatment time 10s-120s, and treatment distance 5mm-20mm.
Citation Information
Patent Citations
Composite current collector, preparation process and battery comprising composite current collector
CN117832502A
